Pengaruh Penggunaan Media Torso Terhadap Hasil Belajar IPA Siswa Kelas IV SD YPK Elim Malanu Kota Sorong - Mulatipo, Dwi Agustin; Purwojuono, Ribut; Saputro, Isnaini Eddy (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to find out and describe whether there is an influence of Torso Media on improving the learning achievement of science subjects at fourth grade students, at SD YPK Elim Malanu, Sorong City. In this study, researchers used a multiple choice test which was given twice (pretest and posttest) to 32 students as the research sample. The method used is a quantitative method, with data analysis techniques using the paired sample t test. The results of the research show that there is an influence of Torso Media on improving the learning outcomes of science subjects at fourth grade students. It was seen from 13,806>2.0422, or tcount > ttable, so that Ho is rejected and Ha is accepted. The conclusion is the using of Torso media has a significant effect on improving student learning outcomes in science subjects and based on the sig value, namely 0.00 < 0.05, it can be concluded that Ho is rejected and Ha is accepted. It means that there is an average difference between the pre-test and post-test, and there is an influence from learning using Torso Media on Learning outcomes of fourth grade students at YPK Elim Malanu Elementary School, Sorong City.